2010
DOI: 10.2136/vzj2009.0155
|View full text |Cite
|
Sign up to set email alerts
|

Beech Forest Density Control on the Dominant Water Flow Types in Andic Soils

Abstract: Silvicultural opera ons increasingly aim to achieve desired water-related ecological services of forests and forest soils. Therefore, the eff ects of forest stand density, site, and soil depth on the water fl ow types were studied by conduc ng dye tracer experiments in two montane beech (Fagus sylva ca L.) forests located in the Western Carpathian Volcanic Range, Central Slovakia. Prevalent fl ow types were iden fi ed under usual weather condions. Brilliant Blue FCF dye tracer was periodically applied in powde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…6). Flury et al, 1994;Vanderborght et al, 2001;Capuliak et al, 2010). In this respect, the modified scheme implicitly assumes that the effects of finger flow can be equated with weak macropore flow (see Weiler and Flühler, 2004) in terms of accelerating flow and transport velocities.…”
Section: Class Pedotransfer Functions Classification Systems and Vumentioning
confidence: 99%
“…6). Flury et al, 1994;Vanderborght et al, 2001;Capuliak et al, 2010). In this respect, the modified scheme implicitly assumes that the effects of finger flow can be equated with weak macropore flow (see Weiler and Flühler, 2004) in terms of accelerating flow and transport velocities.…”
Section: Class Pedotransfer Functions Classification Systems and Vumentioning
confidence: 99%
“…Consequently, such soils can have different hydraulic conductivities in horizontal and vertical directions, producing macroscopic anisotropy. This anisotropic behavior can, for example, accelerate hypodermic flow at the hillslope scale and speed up the formation of subsurface flow (Capuliak et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The non-equilibrium flow phenomenon, which penetrates through and bypasses most of the soil matrix and pores along some specific paths, widely exists in heterogeneous, anisotropic permeable media, especially in mountain areas with a complex geological structures [3,4]. In comparison to matrix connective flow, preferential flow is mainly driven by gravity and greatly decreases the contact time and area between the seepage liquid and solid media [5]. It is vital to have an effective buffer for the peak and duration of surface runoff [6,7] for the immediate replenishment of groundwater and required chemical composition [8,9], and to reduce the risks of soil erosion and landslides [10].…”
Section: Introductionmentioning
confidence: 99%
“…Alaoui [19] found that large pores could transport approximately 74-100% of soil water with 0.23-2% of the total soil volume, and that different combinations of preferential types led to different water transfer rates. Studies on the influencing factors of preferential flow have mainly focused on vegetation type and plant roots [5,6,[20][21][22], soil structure [23,24], soil physical properties, and insect activities [25,26].Rock fragments in stony soil also increase the complexity of soil hydrological processes [27]. In the past 20 years, scholars have studied how rock fragments in soil influence soil moisture and solute transport from the aspects of gravel type, particle size, shape, content, and their distribution in the soil matrix [28][29][30][31].…”
mentioning
confidence: 99%
See 1 more Smart Citation